Morality as a Boundary Condition in Fraud Prevention: Evidence from Village Fund Management - Yuni Lestari Br Sitepu; Juni Anggraini; Jayne Amita Ompusunggu (Jurnal Ilmiah Accusi, 2026)
This study examines the effect of apparatus competence and internal control systems on fraud prevention in village fund management, with morality acting as a moderating variable in villages within Lae Parira District, Dairi Regency, North Sumatra. The study employs a quantitative approach using primary data collected through questionnaires distributed to village officials directly involved in village financial management. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with the assistance of SPSS software. The findings reveal that apparatus competence does not have a significant effect on fraud prevention, while the internal control system has a positive and significant effect on fraud prevention. However, morality is not able to strengthen the relationship between apparatus competence, internal control systems, and fraud prevention in the moderated model. These findings suggest that fraud prevention in village fund management does not solely depend on individual competence or moral values, but also requires consistent supervision and effective governance practices within village administration